XIAP BIR domain suppresses miR-200a expression and subsequently promotes EGFR protein translation and anchorage-independent growth of bladder cancer cell. Issue 1 (December 2017) - Huang, Chao; Zeng, Xingruo; Jiang, Guosong; Liao, Xin; Liu, Claire; Li, Jingxia; Jin, Honglei; Zhu, Junlan; Sun, Hong; Wu, Xue-Ru; Huang, Chuanshu
Abstract Background The X-linked inhibitor of apoptosis protein (XIAP) is a well-known potent apoptosis suppressor and also participates in cancer cell biological behaviors, therefore attracting great attentions as a potential antineoplastic therapeutic target for past years. Anti-IAP therapy is reported to be closely related to epidermal growth factor receptor (EGFR) expression level. However, whether and how XIAP modulates EGFR expression remains largely unknown. Methods Human XIAP was knockdown with short-hairpin RNA in two different bladder cancer cell lines, T24T and UMUC3. Two XIAP mutants, XIAP ∆BIR (deletion of N-terminal three BIR domains) and XIAP ∆RING (deletion of C-terminal RING domain and keeping the function of BIR domains), were generated to determine which domain is involved in regulating EGFR. Results We found here that lacking of XIAP expression resulted in a remarkable suppression of EGFR expression, consequently leading to the deficiency of anchorage-independent cell growth. Further study demonstrated that BIR domain of XIAP was crucial for regulating the EGFR translation by suppressing the transcription and expression of miR-200a. Mechanistic studies indicated that BIR domain activated the protein phosphatase 2 (PP2A) activity by decreasing the phosphorylation of PP2A at Tyr307 in its catalytic subunit, PP2A-C. Such activated PP2A prevented the deviant phosphorylation and activation of MAPK kinases/MAPKs, their downstream effector c-Jun, and in turn inhibiting transcription of c-Jun-regulated the miR-200a. Conclusions Our study uncovered a novel function of BIR domain of XIAP in regulating the EGFR translation, providing significant insight into the understanding of the XIAP overexpression in the cancer development and progression, further offering a new theoretical support for using XIAP BIR domain and EGFR as targets for cancer therapy.